Liability-Creating Versus Non-Liability-Creating Fiscal Stabilization Policies : Ricardian Equivalence, Fiscal Stabilization, and EMU - Masson, Paul (IMF Working Papers; Working Paper ;, 1998)
This paper looks at theoretical and empirical issues associated with the operation of fiscal stabilizers within an economy. It argues that such stabilizers operate most effectively at a national, rather than local, level. As differing cycles across regions tend to offset each other for the country as a whole, national fiscal stabilizers are not associated with the same increase in future tax liabilities for the region as local ones. Accordingly, the negative impact from the Ricardian effects associated with these tax liabilities is smaller. Empirical work on data across Canadian provinces indicates that local stabilizers are only 1/3 to 1\2 as effective as national stabilizers that create no future tax liability.